2020
DOI: 10.1007/s11356-020-10467-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined ultrasound-ozone treatment for reutilization of primary effluent—a preliminary study

Abstract: The present work is a preliminary study on the potential of low-frequency ultrasound irradiation coupled with O 3 process for the disinfection of a primary effluent from a municipal wastewater treatment plant preserving nutrient levels (in particular nitrogen and phosphorous), for its possible reuse in civil, industrial, and agricultural sectors. The treated water could be reused, after appropriate dilution, contributing to the circular economy perspective and reducing the need for both chemical fertilizer add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Nitrogen showed a trend similar to that of carbon in ozonated sewage samples, i.e., a slight variation and no significant difference between doses. Rossi et al (2021) also observed a similar result when studying the effect of ozone and ultrasound on the agricultural reuse of primary effluents. On the other hand, these authors reported that a slight increase in TN would probably be related to a release of nitrogen material from particulate organic matter.…”
Section: Resultssupporting
confidence: 58%
“…Nitrogen showed a trend similar to that of carbon in ozonated sewage samples, i.e., a slight variation and no significant difference between doses. Rossi et al (2021) also observed a similar result when studying the effect of ozone and ultrasound on the agricultural reuse of primary effluents. On the other hand, these authors reported that a slight increase in TN would probably be related to a release of nitrogen material from particulate organic matter.…”
Section: Resultssupporting
confidence: 58%
“…Elwakeel et al [6] pointed out that magnetic thiourea-formaldehyde polymer loaded with silver ion provides a promising disinfectant activity against microbial pathogens in the water and wastewater samples with high magnetic-separation ability. Additionally, since there are many modern technologies available, appropriate polishing treatment for water reuse can be selected based on a "fit-for -purpose" approach [7].…”
Section: -Day Biologicalmentioning
confidence: 99%
“…There are numerous chemical techniques which have been employed in wastewater treatment, such as chemical coagulation [1], Fenton reaction [2], ion exchange [3], precipitation [4], combined ultrasound-ozone [5], ultra-filtration [6], electrochemical techniques [7], adsorption [8][9][10], and packed columns in water treatment applications [11,12] to eliminate trace and heavy elements, micropollutants and other hazardous materials (i.e., biochemical oxygen demand (BOD), chemical oxygen demand (COD), paint, phenol, oil and grease, total suspended solids (TSS), and coliform bacteria) from industrial, municipal and drainage wastewaters, and aqueous media [1]. Among all of the above-mentioned techniques, adsorption in clay minerals is viewed as an especially powerful procedure, particularly regarding the use of low-cost, biodegradable, and environmentally-friendly materials for the removal of pollutants from wastewaters and aqueous solutions [13].…”
Section: Introductionmentioning
confidence: 99%